Indonesian EFL Students’ Elastic Language in Discussing Horror Movies - Putri Rindu Kinasih; Jazlyn Lacey (Journal of English Language Teaching and Linguistics, 2024)
To create an exchange of information is the goal of communication. Surprisingly, we rarely express ourselves clearly, precisely, and explicitly when we write or speak. This research is a conversational analysis (CA) that studies eight students from the 5th semester of the English Department of a private university. The 21’23”- conversation about the Indonesian horror movie is analyzed based on the classification of four lexical categories and categories of EL’s pragmatic function elastic language proposed by Zhang (2015). This research aims to identify the implied messages conveyed by women and men as they talk about Indonesian horror movies. The study showed that approximate stretchers are the most used kind of elastic language. And, men and women use approximate stretchers at similar rates. The same number of approximate stretchers opposes the claim that women are less assertive. Then, women tend to use more intensifiers, which enhances interaction in communication. The last finding of this study was that women employed more epistemic stretchers than men. Additionally, this research finds that both men and women used elastic language for just-right elastic function mainly. Because approximation is frequently sufficient in this situation, approximate stretchers are usually chosen for just-right elastic terms.